Obligatory protective vaccinations and the implementation of parental authority: A study of judicial decisions in the area of legal liability - Zieliński, Grzegorz; Kanecki, Krzysztof; Nitsch-Osuch, Aneta; Tyszko, Piotr (Family Medicine & Primary Care Review, 2019)
The number of people who are afraid of vaccinations and who refuse to submit their children to them is constantly growing in Poland. Certain attempts are being made to change legal provisions regarding the obligation of preventative vaccinations. An important element of this discussion is an analysis of the current legal solutions included in judicial decisions. The aim of this paper is to present court judgements in cases regarding legal responsibility related to the obligation of preventative vaccinations issued by the Supreme Court, district courts, the Supreme Administrative Court and voivodship administrative courts. The subject of the judgments under discussion were, in particular, matters relating to the obligation to undergo mandatory vaccinations; legal sources of the obligation to undergo preventative vaccinations, included in the Announcement of the Chief Sanitary Inspector on the protective vaccine program; mandatory preventative vaccinations and the constitutional rights of citizens; administrative enforcement of the obligation to subject a child to mandatory preventative vaccinations, as interpreted by the state, and contraindications to vaccination; enforced fulfillment of the obligation to subject a child to preventative vaccination, and the legal effect of the refusal to subject a child to a pre-vaccination screening; the use of fines to enforce mandatory preventative vaccinations; administrative fines and criminal liability for failure to undergo vaccinations against infectious diseases; parental refusal to subject a child to mandatory vaccinations; civil liability for compensation; and nature and the enforcement of a parents’ obligation to subject children to protective vaccination. The administrative and criminal law measures provided for in the Act on enforcement procedure in administration, including fines, to enforce the statutory obligation of vaccination may be used to achieve this goal. This has been concluded in judgements which are valid.